Quantitative Determination of Ivermectin in Raw Milk Using Positive ESI LC-MS/MS - Meenakshi Dahiya; Shanta Sen; Kiran Lamba; Manjeet Aggarwal; R. K. Khandal (E-Journal of Chemistry)
Ivermectin, a veterinary drug, is commonly used endectocide for animal husbandry. The drug is available in the form of subcutaneous or topical formulations. Its application may cause accumulation of its residues into the animal tissues, which ultimately find their way into the food products, such as milk and meat products. In order to determine the residues of ivermectin in milk, a comparatively simple, sensitive and rapid method was developed and validated using LC-MS/MS. The MRM transitions corresponding to m/z 892.71>569.6, 892.71>551.5 and 892.71>307.3 were used for the purpose of quantification and evaluation of other parameters of the method. The limit of detection of the method was found to be 0.1 μg/kg and the limit of quantitation was calculated as 0.2 μg/kg. The method was found to be linear in the range of 1.0 ng/mL to 100.0 ng/mL with correlation coefficient of 0.9992 for pure calibration curve and 0.9990 for the matrix- matched calibration curve. The recoveries of ivermectin from the spiked samples of raw milk were found between 85 to 105%.